2016
DOI: 10.1038/jp.2016.66
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of lawsuits related to point-of-care ultrasonography in neonatology and pediatric subspecialties

Abstract: This study of a major legal database suggests that POCUS use and interpretation is not a significant cause of lawsuits against neonatologists and PSS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 28 publications
1
29
0
1
Order By: Relevance
“…Another major barrier identified in this study was the lack of trained ultrasound personnel to instruct fellows and faculty in ultrasound scanning techniques. Somewhat surprisingly, legal concerns over point‐of‐care sonography in the NICU was not a chief concern, which is consistent with a recent analysis of a noteworthy legal database in the United States that suggested point‐of‐care sonography use and interpretation is not a substantial source of lawsuits against neonatologists and pediatric subspecialists …”
Section: Obstacles For Adoption Of Bedside Sonography In Neonatologysupporting
confidence: 75%
“…Another major barrier identified in this study was the lack of trained ultrasound personnel to instruct fellows and faculty in ultrasound scanning techniques. Somewhat surprisingly, legal concerns over point‐of‐care sonography in the NICU was not a chief concern, which is consistent with a recent analysis of a noteworthy legal database in the United States that suggested point‐of‐care sonography use and interpretation is not a substantial source of lawsuits against neonatologists and pediatric subspecialists …”
Section: Obstacles For Adoption Of Bedside Sonography In Neonatologysupporting
confidence: 75%
“…Another common concern regarding implementation of a point‐of‐care US curriculum was the potential for lawsuits (13.6%) related to the use of point‐of‐care US. To our knowledge, there are no studies evaluating lawsuits related to point‐of‐care US use in internal medicine, although studies assessing other specialties indicate that concerns are likely overinflated . Reviews of a major US legal database (Westlaw database) revealed no cases of lawsuits related to the interpretation or performance of point‐of‐care US examinations over 25 years in neonatology and pediatric subspecialties and over 20 years in EM .…”
Section: Discussionmentioning
confidence: 99%
“…This kind of negativity has been previously reported. 14,15 From this study, there seems to be fear among the radiologists and sonographers that their territory is being invaded by cadres in the health care system and as such may lose their own professional identity and their roles in the healthcare team. POCUS training for nonradiology professionals has been previously reported with some level of success.…”
Section: Discussionmentioning
confidence: 89%
“…8 Similar POCUS training programmes have been reported elsewhere. [9][10][11][12][13][14][15] In Uganda, where this study was conducted, maternal mortality due to pregnancy-related complications remains high especially in rural communities. Some of these pregnancy-related complications can be detected early during obstetric ultrasound and timely management effected.…”
Section: Introductionmentioning
confidence: 99%